2020
DOI: 10.3389/fcvm.2020.00019
|View full text |Cite
|
Sign up to set email alerts
|

The Inconsistent Nature of Heart Rate Variability During Sleep in Normal Children and Adolescents

Abstract: Conclusion:Our results demonstrate that there are considerable changes in the spectral analysis of cardiac function occurring during different sleep stages and between sleep cycles across the night. Hence, time of night and sleep stage need to be considered when reporting any HRV differences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 57 publications
3
6
0
Order By: Relevance
“…Notably, we also underscore the individual variability of HRV analyses, finding that group-level differences were largely driven by highly significant changes in a minority of subjects (Table 4). This result highlights the caution that must be taken with HRV interpretation; we suggest future studies on intra-individual HRV analyses account for potentially mediating factors that may affect autonomic regulation, such as time of night [22].…”
Section: Example Application: Hrv In Wakefulness and Sleepmentioning
confidence: 85%
“…Notably, we also underscore the individual variability of HRV analyses, finding that group-level differences were largely driven by highly significant changes in a minority of subjects (Table 4). This result highlights the caution that must be taken with HRV interpretation; we suggest future studies on intra-individual HRV analyses account for potentially mediating factors that may affect autonomic regulation, such as time of night [22].…”
Section: Example Application: Hrv In Wakefulness and Sleepmentioning
confidence: 85%
“…Overall, these modifications in children without OSA (mainly snorers) were similar to those observed by Kontos et al . in 75 healthy children and adolescents (Kontos et al., 2020). It is usually stated that there is a shift of cardiac autonomic modulation across sleep stages in the direction of more parasympathetic modulation from wake to NREM sleep, and a reversal to a balance of less parasympathetic modulation entering REM sleep (Elsenbruch et al., 1999), which may seem to contradict our present results.…”
Section: Discussionmentioning
confidence: 99%
“…The minute following an event was also discarded from the analysis (Stein & Pu, 2012). We standardised the epoch of both NREM and REM sleep according to the results of Kontos et al obtained in a large sample of healthy children (n = 75) who showed that maximal differences in HRV indices can be expected from these two epochs (NREM1 and REM1 epochs) (Kontos et al, 2020). Furthermore, children with OSA have normal sleep stage distribution and OSA is predominantly a REM phenomenon in children (Goh et al, 2000).…”
Section: Heart Rate Variability Analysesmentioning
confidence: 99%
“…During sleep, the respiration rate in toddlers may be 18 min −1 or even lower, but it may be higher than 24 min −1 as well. That is, automatic segmental analysis of a 24 h ECG recording with a narrowly restricted frequency range would most probably fail or at least provide different information compared to SD1 (or RMSSD) [ 39 ]. Furthermore, this may even hold for pre-selected segments based on strict signal preprocessing and healthy adults, where information content may be lost when the HF band according to the recommended definition is used without further consideration.…”
Section: Discussionmentioning
confidence: 99%